2007
DOI: 10.1002/jqs.1131
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Quaternary landscape inheritance in Australia

Abstract: Palaeogeographic reconstructions indicate that parts of the Australian continent have been subaerially exposed for hundreds of millions of years. Some landforms and regolith are demonstrated to be at least 300 million years old, but their persistence at or near the surface is inconsistent with long-term denudation rate estimates based on cosmogenic nuclides and apatite fission track thermochronology. Burial and exhumation are suggested as significant preservation factors, in conjunction with prolonged tectonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…Antecedent controls on contemporary river character and behaviour are particularly prevalent in this tectonically-passive landscape setting where preservation of palaeovalleys and palaeosediments is common (Bishop, 2007;Pillans, 2007). When placed in context of the spectrum of river diversity found in partly confined settings, the examples highlighted here would be considered "inactive" in terms of their capacity to adjust and the recurrence of floodplain formation and reworking.…”
Section: Partly Confined Rivers and The Spectrum Of River Diversitymentioning
confidence: 93%
See 2 more Smart Citations
“…Antecedent controls on contemporary river character and behaviour are particularly prevalent in this tectonically-passive landscape setting where preservation of palaeovalleys and palaeosediments is common (Bishop, 2007;Pillans, 2007). When placed in context of the spectrum of river diversity found in partly confined settings, the examples highlighted here would be considered "inactive" in terms of their capacity to adjust and the recurrence of floodplain formation and reworking.…”
Section: Partly Confined Rivers and The Spectrum Of River Diversitymentioning
confidence: 93%
“…They found that only localised adjustment to channels and floodplains had occurred in partly confined valleys and that the imprint of human disturbance has been relatively limited. Geological and climatic controls ensure that there is significant geomorphic memory in this old, slowly downwearing landscape (Pillans, 2007) and that contemporary processes and forms are not always the result of current climatic conditions or human-induced impacts.…”
Section: Antecedent Controls On Contemporary River Forms and Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, Old and Ancient Landscapes are widespread in Australia (e.g. Jutson 1914;Twidale 1997;Pillans 2007;Vasconcelos et al 2010). In fact many of the Australian landscapes would qualify as old (following our criteria), and the Kimberley Plateau (northern top of Western Australia) is among the oldest continuously exposed landforms on Earth, sub-aerially exposed since the Precambrian-more than 540 Ma (Ollier et al 1988;Gale 1992;Pillans 2007).…”
Section: Landscape Antiquity and Nutrient Status Of Soilsmentioning
confidence: 93%
“…Jutson 1914;Twidale 1997;Pillans 2007;Vasconcelos et al 2010). In fact many of the Australian landscapes would qualify as old (following our criteria), and the Kimberley Plateau (northern top of Western Australia) is among the oldest continuously exposed landforms on Earth, sub-aerially exposed since the Precambrian-more than 540 Ma (Ollier et al 1988;Gale 1992;Pillans 2007). Yet the temporal scale discrepancies between the age of the surface and omnipresent rejuvenation processes give rise to nontrivial questions such as: Is the long-term tranquil geological period of any importance to the evolution of plants, the persistence of old lineages, or to plant community assembly?…”
Section: Landscape Antiquity and Nutrient Status Of Soilsmentioning
confidence: 97%